Plantar comunidades: Elementos para a igreja semear a boa nova em áreas pioneiras - Luis Gessner, George (Vox Scripturae - Revista Teológica Internacional, 2010)
The research, named Plant Communities: Elements to the IECLB sow the good news in pioneer areas, treats important elements of the planting communities proposal. It intents to develop a base for missionary activity in the church. Thus, it develops an understanding of the issue through the construction of a historical overview, an analysis of the terms plant and communities taken separately and the formulation of a concept. The research also presents the biblical and theological foundations of the theme from the mandate of Jesus Christ in the great commission and its application in the early Christian community. And, from all these impulses, it highlights important elements of the plantation of communities, deepening them. The elements addressed are: a commissioning, which takes into account the dimension of the call and the prayer, a preparation that makes a team and identify the target audience; an evangelistic contact, which assimilates the local context and starts from a core group, an evangelistic preaching, that is contextualized and calls for a commitment to Jesus Christ, and the formation of a new community, which makes disciples and engages missionary. It concludes without an elaboration of importance order among the elements, but emphasizes the importance of taking the local reality into account. It also warns about the danger of reducing the mission of God or the plant communities to mere work of man, not considering that it is, f irstly, work of God.
Keywords: Plant communities; Igreja Evangélica de Confissão Luterana no Brasil; elements; missionary ministry